PENERAPAN KEGIATAN MARKET DAY UNTUK MENINGKATKAN KARAKTER KEWIRAUSAHAAN ANAK USIA 5-6 TAHUN DI TK PUSPAGIRI KABUPATEN TASIKMALAYA - Ajang Ramdani; Alika Mutiara (Program Studi Pendidikan Islam Anak Usia Dini, 2025)
This study was motivated by the low entrepreneurial character of children aged 5–6 years at TK Puspagiri, as reflected in their limited creativity, independence, responsibility, cooperation, and self-confidence. These conditions were caused by less optimal learning methods and the lack of active roles from teachers and parents in instilling entrepreneurial values. The study aimed to examine the planning, implementation, and outcomes of the Market Day activity in fostering entrepreneurial character in early childhood. The research employed Classroom Action Research (CAR) using the Kemmis and McTaggart model conducted in three cycles, with 10 children from group B1 as subjects. Data were collected through observation and documentation. The findings indicated that Market Day significantly improved entrepreneurial indicators: children became more creative in decorating products, independent in managing roles, responsible for their merchandise, cooperative, and confident in social interactions. In conclusion, Market Day proved to be an effective contextual method, and further studies may integrate it with environmental-based entrepreneurship or simple digitalization to enrich children’s learning experiences